2017
DOI: 10.1097/mao.0000000000001527
|View full text |Cite
|
Sign up to set email alerts
|

Audiometric Outcomes Following Endoscopic Ossicular Chain Reconstruction

Abstract: Controlling for the type of prosthesis, there were no significant differences in hearing outcomes with respect to staged ossicular chain reconstruction or whether the endoscope or microscope was used for visualization. Thus, in this series, endoscopic OCR yields similar audiometric outcomes when compared with microscopic OCR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 23 publications
5
26
1
Order By: Relevance
“…However, in the long‐term perspective, there is apparently no significant advantage of the endoscopic over microscopic technique. Yawn et al reported similar audiometric outcomes in their study …”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…However, in the long‐term perspective, there is apparently no significant advantage of the endoscopic over microscopic technique. Yawn et al reported similar audiometric outcomes in their study …”
Section: Discussionsupporting
confidence: 68%
“…Yawn et al reported similar audiometric outcomes in their study. 12 The complications encountered in our study were redevelopment of retraction pocket, displacement of the prosthesis, prosthesis extrusion, and graft failure. Similar incidences of complications were noted in both techniques, which was statistically insignificant.…”
Section: Discussionmentioning
confidence: 79%
“…A previous study reported that the post-operative hearing outcomes were better in the endoscopic ossicular chain reconstruction group than in the microscopic ossicular chain reconstruction group; however, this result was attributed to the better pre-operative hearing levels of the endoscopic ossicular chain reconstruction cases. 1 In order to eliminate such confounding factors, we compared the pre-operative hearing characteristics of patients who underwent endoscopic and microscopic ossicular chain reconstruction, and did not find any differences between the groups (Table 2). Because post-operative hearing outcomes after ossicular chain reconstruction may be influenced by the type of the ossicular chain reconstruction material or technique, 21 as well as the status of the middle-ear mucosa and Middle Ear Risk Index category, 22 we attempted to exclude the potential effects of these factors on post-operative hearing results by ensuring that the endoscopic and microscopic groups were matched in terms of their peri-operative features (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Fixation or erosion of the malleus, incus or stapes can be repaired using a tympanoplasty approach using either autologous material or prosthetic materials (PORP-partial ossicular replacement prosthesis, TORP-total ossicular replacement prosthesis). Cartilage is used to cover ossicular prosthetics, except for stapes implants, as these will typically extrude or become exposed through the tympanic membrane without coverage [11]. Explantation of middle ear prosthetics rarely if ever necessitates pathologic examination.…”
Section: Common Surgical Proceduresmentioning
confidence: 99%